Peran Perempuan dalam Ibadah: Dialektika Politik dan Teologi Tubuh - Agus Surya (Sekolah Tinggi Teologi Paulus Medan, Sumatra Utara, 2020)
This paper presents an analysis of the text of 1 Timothy 2: 8-12 in relation to the role of women in worship. Where will be studied in the dialectic of body politics and body theology. The study in this paper uses a qualitative descriptive method. Data were collected using literature study techniques. The results of the study illustrate that the text of 1 Timothy 2: 8-12 presents the role of women in ministry in the Ephesian church. This condition implies that the role of women in church service has the same obligations as men and has the same value before God. Tulisan ini menyajikan analisis teks 1 Timotius 2:8-12 dalam kaitannya dengan peran perempuan dalam ibadah. Dimana akan dikaji dalam dialektika politik tubuh dan teologi tubuh. Kajian dalam tulisan ini menggunakan metode deskriptif kualitatif. Data dikumpulkan dengan teknik studi pustaka. Hasil penelitian memberikan gambaran bahwa teks1 Timotius 2:8-12 menyajikan peran perempuan dalam pelayanan di jemaat Efesus. Kondisi ini berimplikasi bahwa peran perempuan dalam pelayanan jemaat memiliki kewajiban yang sama dengan laki-laki, serta memiliki nilai yang sama di hadapan Allah.